2016
DOI: 10.1007/s40279-016-0562-5
|View full text |Cite
|
Sign up to set email alerts
|

Current Approaches to Tactical Performance Analyses in Soccer Using Position Data

Abstract: Tactical match performance depends on the quality of actions of individual players or teams in space and time during match-play in order to be successful. Technological innovations have led to new possibilities to capture accurate spatio-temporal information of all players and unravel the dynamics and complexity of soccer matches. The main aim of this article is to give an overview of the current state of development of the analysis of position data in soccer. Based on the same single set of position data of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
247
0
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(262 citation statements)
references
References 34 publications
7
247
0
8
Order By: Relevance
“…Advances in technology and access to global positioning system (GPS) tracking devices have enabled the collection of large volumes of training data (Castellano, Silva, Usabiaga & Barreira, 2016;Travassos, Vilar, Araújo, & McGarry, 2014b) and expanded the possibilities for interpreting team performance in 11-a-side soccer (Memmert, Lemmink, & Sampaio, 2016). Moreover, numerous studies have shown how the use of task constraints in training situations leads to changes in indicators of collective performance.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in technology and access to global positioning system (GPS) tracking devices have enabled the collection of large volumes of training data (Castellano, Silva, Usabiaga & Barreira, 2016;Travassos, Vilar, Araújo, & McGarry, 2014b) and expanded the possibilities for interpreting team performance in 11-a-side soccer (Memmert, Lemmink, & Sampaio, 2016). Moreover, numerous studies have shown how the use of task constraints in training situations leads to changes in indicators of collective performance.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed methodology on this paper can be extended in order to describe football teams and also for performing more general tactical analyses (Memmert, Lemmink, & Sampaio, 2017). Teams could be clustered according to previously well-defined indicators of performance (Cintia, Giannotti, Pappalardo, Pedreschi, & Malvaldi, 2015), which allow to find characteristics associated to similar football teams, for example, with they play style (Gyarmati, Kwak, & Rodriguez, 2014) or even to predict and explain match outcomes (Spencer, Morgan, Zeleznikow, & Robertson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There is a large number of such quite simple indicators (for a recent overview: Memmert, Lemmink, & Sampaio, 2017) They all have in common that they do not say much about the playing process, the tactical quality, or the success of actions in defence or offence (Memmert et al, 2017). Different from these indicators, the presented approach tries to adapt "success" directly to the process dynamics, measuring it in terms of economics.…”
Section: Introductionmentioning
confidence: 99%